2007
DOI: 10.1093/treephys/27.10.1493
|View full text |Cite
|
Sign up to set email alerts
|

Fine root biomass in relation to site and stand characteristics in Norway spruce and Scots pine stands

Abstract: Variations in fine root biomass of trees and understory in 16 stands throughout Finland were examined and relationships to site and stand characteristics determined. Norway spruce fine root biomass varied between 184 and 370 g m(-2), and that of Scots pine ranged between 149 and 386 g m(-2). In northern Finland, understory roots and rhizomes (< 2 mm diameter) accounted for up to 50% of the stand total fine root biomass. Therefore, the fine root biomass of trees plus understory was larger in northern Finland in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
164
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(195 citation statements)
references
References 43 publications
23
164
1
7
Order By: Relevance
“…Thus, pine in general may produce fewer fine roots in peatland forests when the soil nutrient status is better. Similar patterns have also been found for Scots pine FRP in boreal mineral-soil forests (Helmisaari et al 2007;Kalliokoski et al 2010). Thus, the FRP patterns of individual species may differ from the pattern in total FRP, which in our study increased with soil nutrient status.…”
Section: Betula Pubescenssupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, pine in general may produce fewer fine roots in peatland forests when the soil nutrient status is better. Similar patterns have also been found for Scots pine FRP in boreal mineral-soil forests (Helmisaari et al 2007;Kalliokoski et al 2010). Thus, the FRP patterns of individual species may differ from the pattern in total FRP, which in our study increased with soil nutrient status.…”
Section: Betula Pubescenssupporting
confidence: 86%
“…The soil nutrient regime also influences both fine-root biomass (FRB) and FRP; however, the directions of the responses have varied among studies in different ecosystems (Santantonio et al 1977;Keyes and Grier 1981;Leibundgut 1981;Hendricks et al 2006), and the measures of soil nutrients reported in individual studies have not allowed for a systematic synthesis (Finér et al 2011). Yet, in the Boreal Zone, most results suggest higher FRB or FRP at poorer sites (Helmisaari et al 2007;Yuan and Chen 2010;Lehtonen et al 2016). For peatlands, the scarce observations so far available suggest a contrasting pattern Laine 1998, 2000;Laiho et al 2014).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, fine root could be used as a sensitive indicator of changes in tree physiological traits and environmental conditions [3,12]. Previous results have demonstrated that fine root biomass is dependent upon a wide range of both biotic and abiotic factors, such as climatic conditions (geographical location, precipitation, elevation and annual temperature), soil properties (texture, moisture, chemistry, nutrient availability), and stand characteristics (basal area, stand density, stand age, tree species, and intra-and interspecific competition between plants) [13,14].…”
Section: Introductionmentioning
confidence: 99%